Miniature Design of Liquid Filling Machine Automatically Using ESP32 Based IOT (Internet of Things) - Ariski Munandar; Nuri David Maria Veronika; Dedy Abdulllah; Eka Sahputra (Penerbit Jurnal Indonesia, 2023)
This study aimed to design automatic liquid filling on miniature machines to make it easier to use by making volume control innovations on automatic liquid filling machines, and design an IOT system for filling automatic liquid machines by using esp32. The data collection method of this study was literature or literature studies. The data processing of this study was qualitative processing of performing data centering. Presentation of data was done in order to easily draw conclusions and take further action. The overall discussion of the tool was the final test after all components run smoothly. The components were placed based on the function of each component so that the tool can look neater and function properly. As an application for testing ESP32 microcontrollers, push buttons, ultrasonic sensors, and relays. The tool released liquid when the push button was pressed according to the desired volume selection. The overall test was carried out with 2 variations of liquid volume, namely 350 ml and 450 ml. The result of testing the liquid output from the tool show that from the 350 ml volume test which was the output of the push button/button 1. It can be seen from the results of measurements by using a measuring cup which was not much different from the setpoint of 350 ml and had a liquid filling time of about 7 seconds out of 10 experiments. It means that the input button 1 with a setpoint of 350 ml is successful and very close to the setpoint given. The test results for a volume of 450 ml which is the output of push button / button 1. It can be seen that the results of measurements by using a measuring cup are not much different with a setpoint. of 450 ml and a liquid filling time of about 9 seconds out of 10 experiments. Based on the results of the study can be concluded that from the input button 1 with a setpoint of 450 ml is successful and very close to the given setpoint. The liquid that has been using the manual method. The liquid volume control innovation is designed by using two push button buttons. With one push button for 350 ml liquid variations and another push button for 450 ml liquid variations. The IoT monitoring works well by using an ultrasonic sensor as a liquid level meter and the blynk application as a liquid level display.